INTERFAITH HARMONY GOVERNANCE: A QUINTUPLE HELIX MODEL FOR COLLABORATIVE POLICY IMPLEMENTATION OF RELIGIOUS VALUES AND TOLERANCE IN INDONESIA - Priyanda, Vandyarman Mulya; Hidayati, Mainita (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
This study addresses a critical gap in the literature on interfaith harmony in Indonesia, where existing research predominantly emphasizes normative principles of Pancasila while offering limited analytical models that map multi‑actor collaboration in policy implementation. The purpose of this study is to develop a conceptual framework for collaborative policy implementation using the Quintuple Helix model to strengthen the institutionalization of religious values and tolerance. A qualitative research design was employed, drawing on policy documents and academic literature published between 2000 and 2025. Data were analyzed through systematic literature review procedures, including screening, thematic coding, and conceptual synthesis. The analysis was guided by the Quintuple Helix framework to identify actor roles, interaction patterns, and governance mechanisms. The findings reveal three key insights. First, effective promotion of religious values and tolerance requires coordinated engagement among government, academia, civil society, the private sector, and media. Second, the state remains the primary driver of interfaith harmony, yet non‑state actors contribute essential knowledge, social capital, and communication functions. Third, existing governance arrangements remain fragmented, indicating the need for a more integrated collaborative model. These findings imply that interfaith harmony policies must shift from normative dissemination toward structured multi‑actor governance. The study concludes by proposing a Quintuple Helix–based model that offers theoretical advancement in religious harmony governance and practical guidance for policymakers designing collaborative interfaith programs. Abstrak Penelitian ini mengisi kesenjangan penting dalam studi mengenai kerukunan antarumat beragama di Indonesia, di mana studi terdahulu lebih banyak menekankan prinsip normatif Pancasila dan belum menyediakan model analitis yang memetakan kolaborasi multiaktor dalam implementasi kebijakan. Tujuan artikel ini adalah mengembangkan kerangka konseptual untuk implementasi kebijakan kolaboratif dengan menggunakan model Quintuple Helix guna memperkuat internalisasi nilai-nilai keagamaan dan toleransi. Penelitian ini menggunakan desain kualitatif dengan memanfaatkan dokumen kebijakan dan literatur akademik yang terbit antara tahun 2000 hingga 2025. Data dianalisis melalui prosedur tinjauan pustaka sistematis, termasuk penyaringan, pengodean tematik, dan sintesis konseptual. Analisis dipandu oleh kerangka Quintuple Helix untuk mengidentifikasi peran aktor, pola interaksi, dan mekanisme tata kelola. Temuan penelitian menunjukkan tiga hal utama. Pertama, promosi nilai keagamaan dan toleransi yang efektif memerlukan keterlibatan terkoordinasi antara pemerintah, akademisi, masyarakat sipil, sektor swasta, dan media. Kedua, negara tetap menjadi penggerak utama kerukunan antarumat beragama, namun aktor non-negara menyediakan kontribusi penting berupa pengetahuan, modal sosial, dan fungsi komunikasi. Ketiga, pengaturan tata kelola yang ada masih terfragmentasi sehingga memerlukan model kolaboratif yang lebih terintegrasi. Temuan ini mengimplikasikan perlunya pergeseran kebijakan kerukunan dari pendekatan normatif menuju tata kelola multiaktor yang terstruktur. Studi ini menyimpulkan dengan menawarkan model berbasis Quintuple Helix yang memberikan kontribusi teoretis bagi tata kelola kerukunan beragama serta panduan praktis bagi pembuat kebijakan dalam merancang program kolaboratif lintas aktor.